Communication lines management system - Wong, Kwai Yinn (2008)
The purpose of this project is to develop a RBDMS DSS with OLAP capabilities that will assist management in making decision concerning MAF communications assets. The DSS is to perform general database functions; generate assets and users reports and summaries. The ROLAP model was implemented to provide the DSS with OLAP functionality assisting the system in database queries and analysis. The methodology adopted for the project development is SDLC and model used is Waterfall. Analyzing and development of design requirements are done with the Unified Modeling Language 2.0; the industry standard graphical notation modeling language for object-oriented systems. The system is implemented as a 3 tier web application using an Apache Tomcat Server/JSP container implementing Java Servlet/JSP in a client-server environment running on the organization intranet. The RDBMS were implemented using MySQL 5.0 Community Server and OLAP functionality using Mondrian Server supported by JPivot and WCF. The system prototype were successfully implemented within the project timeframe by setting achievable objectives; adopting the right development methodology; using the appropriate software technologies and close cooperation with organization staff. It is found that the initial documentation of the SRS and SDD greatly assisted the software developed at the later stage. The implementation of the ROLAP model to support the DSS is found to be suitable for organization with existing database structures. It is also found that all the Open Source software’s utilized are capable of developing the required system besides freeing organization resource for other avenues as there are offered under the GNU GPL license. There are also freely available and their usages supported by the Malaysia Open Source IT initiatives.